2020
DOI: 10.1002/elsc.201900163
|View full text |Cite|
|
Sign up to set email alerts
|

Surfactin production in the bioreactor: Emphasis on magnetic nanoparticles application

Abstract: Surfactin is one of the main lipopeptide biosurfactants produced by different species of Bacillus subtilis. This study aims to analyze the effect of starch‐coated Fe0 and Fe3+ nanoparticles on the biomass and biosurfactant production of Bacillus subtilis. Out of 70 soil samples, 20 Bacillus were isolated and genome sequenced by biochemical methods and 16S rRNA gene. Quantitative and qualitative screening methods were used to isolate and detect biosurfactant production. For the aim of this study, 61 and 63 (Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In this study, starch‐coated iron nanoparticles did not show any bacterial toxicity at 1mg/ml and increased the growth rate and production of bio surfactants to 20.62% [19]. Modabber et al., was investigated the effect of starch coated Fe 0 and Fe 3+ nanoparticles on the production of surfactin from Bacillus subtilis [20]. The expression of most Pseudomonas aeruginosa genes is controlled by the Quorum sensing (QS) gene system.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, starch‐coated iron nanoparticles did not show any bacterial toxicity at 1mg/ml and increased the growth rate and production of bio surfactants to 20.62% [19]. Modabber et al., was investigated the effect of starch coated Fe 0 and Fe 3+ nanoparticles on the production of surfactin from Bacillus subtilis [20]. The expression of most Pseudomonas aeruginosa genes is controlled by the Quorum sensing (QS) gene system.…”
Section: Introductionmentioning
confidence: 99%
“…Modabber et al used starch‐coated Fe 3+ and Fe 0 nanoparticles to increase surfactin production. The results showed that the optimal concentration Fe 3+ nanoparticles which has positive effects on the production of bacterial biosurfactants was of 1 mg/L (Modabber et al, 2020). In the study by Young et al, the effect of Fe nanoparticles on increasing surfactant production in Bacillus amyloliquefaciens was investigated.…”
Section: Introductionmentioning
confidence: 99%